Pengaruh Aditif Monoethanolamine (MEA) terhadap Struktur Kristal Copper Tin Oxide - Yulfitrianti, Marlina; Sanjaya, Hary; Budiman, Septian (Darul Yasin Al Sys, 2023)
Solar cell technology is a technology that can create electrical energy using semiconductor devices that have p-n connections. Copper tin oxide CuSnO3 (CSO) is an amorphous oxide semiconductor with a band gap of 2.0–2.5 eV. The method used is sol gel with the addition of one of the commonly used additives, namely Monoethanolamine (MEA). This research aims to determine the effect of monoethanolamine additives on the crystal structure of Copper Tin Oxide using the Sol Gel method. This research is quantitative research by collecting data from previous research and then conducting research using specified methods and objects. The results of research using XRD showed particle sizes ranging from 40.10 – 50.02 nm and the results obtained without additives were 21.06 nm. This is because the addition of additives greatly influences the crystal size and crystal Structure.